Neuroglobin overexpression inhibits oxygen–glucose deprivation-induced mitochondrial permeability transition pore opening in primary cultured mouse cortical neurons - Yu, Zhanyang; Liu, Ning; Li, Yadan; Xu, Jianfeng; Wang, Xiaoying (Neurobiology of disease, 2013)
Neuroglobin (Ngb) is an endogenous neuroprotective molecule against hypoxic/ischemic brain injury, but the underlying mechanisms remain largely undefined. Our recent study revealed that Ngb can bind to voltage-dependent anion channel (VDAC), a regulator of mitochondria permeability transition (MPT). In this study we examined the role of Ngb in MPT pore (mPTP) opening following oxygen–glucose deprivation (OGD) in primary cultured mouse cortical neurons. Co-immunoprecipitation (Co-IP) and immunocytochemistry showed that the binding between Ngb and VDAC was increased after OGD compared to normoxia, indicating the OGD-enhanced Ngb–VDAC interaction. Ngb overexpression protected primary mouse cortical neurons from OGD-induced neuronal death, to an extent comparable to mPTP opening inhibitor, cyclosporine A (CsA) pretreatment. We further measured the role of Ngb in OGD-induced mPTP opening using Ngb overexpression and knockdown approaches in primary cultured neurons, and recombinant Ngb exposure to isolated mitochondria. Same as CsA pretreatment, Ngb overexpression significantly reduced OGD-induced mPTP opening markers including mitochondria swelling, mitochondrial NAD+ release, and cytochrome c (Cyt c) release in primary cultured neurons. Recombinant Ngb incubation significantly reduced OGD-induced NAD+ release and Cyt c release from isolated mitochondria. In contrast, Ngb knockdown significantly increased OGD-induced neuron death, and increased OGD-induced mitochondrial NAD+ release and Cyt c release as well, and these outcomes could be rescued by CsA pretreatment. In summary, our results demonstrated that Ngb overexpression can inhibit OGD-induced mPTP opening in primary cultured mouse cortical neurons, which may be one of the molecular mechanisms of Ngb's neuroprotection. •Neuroglobin (Ngb) can bind to voltage dependent anion channel in cultured neurons.•Oxygen/glucose deprivation-induced mPTP opening was reduced by Ngb overexpression.•Ngb overexpression decreased OGD-induced cytochrome c release from mitochondria.•Recombinant Ngb blocked OGD-induced mPTP opening in isolated mitochondria.•Ngb knockdown in neurons showed enhanced mPTP opening following OGD.